Employee Satisfaction on Remuneration and Fire Safety: Evidence from the Garment Sector of Bangladesh (Journal of Green Business School, 2025)
Workers have difficulties in evaluating their working circumstances due to the constraints of limited knowledge and restricted access to information. This paper aims to assess workers' satisfaction with remuneration and their satisfaction with fire safety in the Bangladesh Ready-Made Garment (RMG) industry, collecting data from primary sources through questionnaire distribution to 252 root-level workers in Narayanganj, Savar (Dhaka), and Gazipur. The findings suggest that although workers are satisfied with the punctuality of their payments and the environment of their workplace, they are worried about the adequacy of their salaries. Despite the availability of fire and health safety equipment, there are gaps in training and knowledge about fire safety. Recommended measures needed to be taken for alleviating the existing dissatisfaction include salary increments, improved working conditions, and periodic fire safety training. The study provides unique insights on current trends in the business, making it a great resource for policymakers, researchers, and practitioners who want a better knowledge of the changing landscape of the RMG sector in Bangladesh. Limitations of this study include a limited sample size and the need for further investigations to determine the impact of the attitude of upper-level workers and the processes for promotion on employee satisfaction.J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 83-97